(untitled) (Jurnal Pembangunan Sosial, 2009)
Malay is typically a Muslim in religion. However, there are still some influences and practices of animism, dynamism, Hinduism and Buddhism that cannot be abolished from their beliefs system. The process of â€œsyncretismâ€ which emerged before and after the presence of Islam has been localized and assimilated into their way of life. This kind of process can clearly be seen in the ritual and traditional practices perform by the Malays who viewed themselves as Muslims. Although these practices are viewed as traditional, the influences, however still has a strong place in the eyes of the Malays. This study aims to explore this interesting issue that has been widely practiced among the Malays and to look at it on the Islamic perspectives.